MicroRNAs in peripheral artery disease: potential biomarkers and pathophysiological mechanisms. (May 2022) - Ring, Andrew; Ismaeel, Ahmed; Wechsler, Marissa; Fletcher, Emma; Papoutsi, Evlampia; Miserlis, Dimitrios; Koutakis, Panagiotis
Peripheral artery disease (PAD) is a disease of atherosclerosis in the lower extremities. PAD carries a massive burden worldwide, while diagnosis and treatment options are often lacking. One of the key points of research in recent years is the involvement of microRNAs (miRNAs), which are short 20-25 nucleotide single-stranded RNAs that can act as negative regulators of post-transcriptional gene expression. Many of these miRNAs have been discovered to be misregulated in PAD patients, suggesting a potential utility as biomarkers for PAD diagnosis. miRNAs have also been shown to play an important role in many different pathophysiological aspects involved in the initiation and progression of the disease including angiogenesis, hypoxia, inflammation, as well as other cellular functions like cell proliferation and migration. The research on miRNAs in PAD has the potential to lead to a whole new class of diagnostic tools and treatments.